Mempertegas Kembali Arah Pembelajaran Bahasa Arab - Dony Handriawan (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2015)
The historical development of the Arabic language in Indonesia can not be separated from the spread of Islam which is the most dominant followed by Indonesian society itself. This has an impact on the development of Arabic learning today, that look is still far from the expected. It seems that view of the cultural and religious patterns of Indonesia in the early 19th century that are still at the level of mythic and theological, less positive effect on the future of Arabic learning in today’s contemporary world. How is the relationship between religion and its influence on the development of the Arabic language, especially in Indonesia will be described in this paper? By using the theory of van Peursen culture and Comte as theoretical analysis, the author tries to find a possible alternative solution of some negative effects in the mythic dimensions of such view, by emphasizing the positive aspects.